Effects of Combined Lemongrass Extract (Cymbopogon citratus) and Physical Exercise on Lipid Profile in Male Wistar Rats (Rattus norvegicus) with Hyperlipidemia Model: A Literatur Review - Pratiwi, Lisa Nabila (International Journal of Ecophysiology, 2025)
Hyperlipidemia remains a significant global health concern as a major risk factor for cardiovascular diseases. This review examines the potential synergistic effects of combining lemongrass (Cymbopogon citratus) leaf extract and physical exercise on improving lipid profiles in hyperlipidemia male Wistar rats. Current evidence suggests that lemongrass extract contains bioactive compounds with antihyperlipidemia properties that can regulate lipid metabolism and exhibit antioxidant effects. Similarly, regular physical exercise improves lipid profiles through various physiological mechanisms. When combined, preliminary studies indicate that lemongrass extract and physical exercise may produce enhanced therapeutic effects in managing hyperlipidemia compared to either intervention alone. The synergistic mechanisms appear to involve improved antioxidant defense systems, enhanced lipid metabolism, reduced lipid peroxidation, and improved insulin sensitivity. This review synthesizes current research findings on this promising combinatorial approach and identifies areas requiring further investigation